2006
DOI: 10.1111/j.1654-1103.2006.tb02434.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of lichen diversity in grass‐dominated vegetation of coastal dunes after wildfire

Abstract: Question: Can lichen diversity of an earlier succession stage be restored in dune grassland after fire in a region with high nitrogen deposition? Location: Calcium‐poor coastal dunes in the Wadden district, The Netherlands. Methods: We sampled dune grassland by using a large continuous transect of 4 m × 4 m blocks on both a south slope and a west slope. The sampling was conducted in the lichen‐rich Violo‐Corynephoretum in 1966, in the vegetation dominated by tall graminoids in 1990 and in the recovering vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The main physiognomical difference was caused by the complete loss of juniper bush patches (Wink andWright 1973, Ónodi et al 2008). Lichens are also shown to have high fire sensitivity (Ketner-Oostra et al 1999), and were especially negatively affected in the present case, which led to the forming of open sand surfaces in the burnt areas, creating micro gaps (Franzese et al 2009). Grass and forb regeneration was already quite advanced by the time of the investigation, but dominance structure was still somewhat different from the original because of the altered physical conditions and presumable biotic interactions during the successional process (Menges and Hawkes 1998).…”
Section: Discussionmentioning
confidence: 67%
“…The main physiognomical difference was caused by the complete loss of juniper bush patches (Wink andWright 1973, Ónodi et al 2008). Lichens are also shown to have high fire sensitivity (Ketner-Oostra et al 1999), and were especially negatively affected in the present case, which led to the forming of open sand surfaces in the burnt areas, creating micro gaps (Franzese et al 2009). Grass and forb regeneration was already quite advanced by the time of the investigation, but dominance structure was still somewhat different from the original because of the altered physical conditions and presumable biotic interactions during the successional process (Menges and Hawkes 1998).…”
Section: Discussionmentioning
confidence: 67%
“…Field studies (Daniëls & Krüger 1996; Ketner‐Oostra et al 2004b; Hasse 2007; Daniëls et al 2008b) suggested that, apart from N deposition, soil organic matter may also be important with respect to the increase of C. introflexus . Hasse (2007), Daniëls et al (2008a, b) and Ketner‐Oostra et al (2004b, 2006) have shown that disturbance (increase in game density, wildfire) of the vegetation cover in acidic cryptogam‐rich grasslands, resulting in exposed organic substrate, temporarily induces the dominance of the species. In order to test whether N deposition increased growth of C. introflexus , and to differentiate between the two factors, C. introflexus was grown in a culture experiment under different N depositions and in soils with different organic matter content.…”
Section: Introductionmentioning
confidence: 99%
“…Other indirect disturbances include damage to the photosynthetic apparatus and the reproductive structures, as a consequence of high air temperature during the fire. Despite this low resistance, certain lichens showed relative resilience to fire events (Yahr, 2000;Ketner-Oostra et al, 2006), being able to re-colonize newly available surfaces and playing a decisive role as pioneer organisms in primary stages of community succession (Garty and Binyamini, 1990;Lawrey, 1991;Favero-Longo et al, 2012).…”
Section: Introductionmentioning
confidence: 98%